Callus induction and plant regeneration of Nepenthes truncata Macf. - Delgado, Danica Riza V. (2007)
Callus induction and plant regeneration of Nepenthes truncate was undertaken to determine the appropriate combination of explant and plant growth regulator for callus induction and for the optimization of the culture medium for callus proliferation and regeneration. Three types of explants were obtained from five-month old axenic seedlings; leaf with pitcher, shoot tip, and nodal segments. These explants were tested in different concentrations of NAA (0.5, 1, 1.5 and 2 mg L-1. Among the explants, leaf proved to be the most suitable for callus induction in ½ strength MS medium and good callus formation was obtained from the combination of 0.5 mg L-1 NAA + 0.05 mg L-1 TDZ. Browning of callus after three to four months was the main constant. To alleviate the problem of browning. Two culture media, ½ strength B5 and ½ strength MS, and two antioxidants/adsorbents, ascorbic acid and activated charcoal were tested against the controls (1/2 strength MS) without antioxidants/adsorbents using leaf as explant. The antioxidants/adsorbents did not seem to control browning but ½ strength MS with activated charcoal regenerated shoots in some treatment s, with a maximum of 7.5 shoots per explant in the combination of 0.5 mg L-1 NAA + 0.05 mg L-1 TDZ. Peptone as an organic supplement for the growth of callus was also studied but its effect was not significant
Thesis (BS Biology) -- University of the Philippines Mindanao, 2007
Keywords: Plant tissue; Plant tissue culture